MLA guide to digital literacy - Carillo, Ellen C. (MLA guides., 2026)
"Helps students understand why digital literacy is a crucial skill for their education, future careers, and participation in democracy. Offers practical guidance for assessing information online and weeding out disinformation and misinformation. Includes a new chapter on generative AI (GenAI). Includes student activities, lesson plans for teachers, and twenty-eight illustrations"-- Provided by publisher.